Gas sensing property of a conducting copolymer - Ak, Metin; Yigitsoy, Basak; Yagci, Yusuf; Toppare, Levent (Walter de Gruyter GmbH, 2007)
Abstract A bifunctional amido thiophene, namely hexamethylene (bis-3-thiophene acetamide) (HMTA) was synthesized and its copolymer with pyrrole was electrochemically prepared in water/PTSA solvent/electrolyte medium. Sensory behavior of this copolymer against ammonia, methanol, dichloromethane (DCM) and n-hexane vapors was investigated. The methanol vapor, which can form hydrogen bonds with the polar groups on the copolymer surface, showed the maximum response. DCM, which is less polar, yielded relatively lower response than methanol. Hexane, being the non-polar vapor, showed the lowest response.
Keywords: Electrolytes; Synthesis; Chemical sensors; Copolymers; Conducting polymers; ammonia; metanol sensing; gas sensor